Cost-benefit Analysis of Maintaining a Fully Stocked Malignant Hyperthermia Cart versus an Initial Dantrolene Treatment Dose for Maternity Units. (August 2018) - Ho, Phi T.; Carvalho, Brendan; Sun, Eric C.; Macario, Alex; Riley, Edward T.
Abstract : What We Already Know about This Topic: Prompt availability of dantrolene is important for treating malignant hyperthermia and has resulted in lowered mortality rates Maintaining a malignant hyperthermia cart and full treatment dose of dantrolene is expensive, particularly for locations with low incidence of malignant hyperthermia, such as labor-and-delivery units What This Article Tells Us That Is New: Cost-benefit analysis showed that the costs associated with maintaining a malignant hyperthermia cart with a full dantrolene supply within 10 min of a maternity unit exceeded the benefits Modeling suggested that a more cost-effective approach would be to keep just an initial dose of dantrolene on the maternity unit, with a central supply of dantrolene available within 30 min Background: The Malignant Hyperthermia Association of the United States recommends that dantrolene be available for administration within 10 min. One approach to dantrolene availability is a malignant hyperthermia cart, stocked with dantrolene, other drugs, and supplies. However, this may not be of cost benefit for maternity units, where triggering agents are rarely used. Methods: The authors performed a cost-benefit analysis of maintaining a malignant hyperthermia cart versus a malignant hyperthermia cart readily available within the hospital versus an initial dantrolene dose of 250 mg, on every maternity unit in the United States. A decision-tree model was used to estimate the expected number of lives saved, and this benefit was compared against the expected costs of the policy. Results: We found that maintaining a malignant hyperthermia cart in every maternity unit in the United States would reduce morbidity and mortality costs by 3, 304, 641 per year nationally but would cost 5, 927, 040 annually. Sensitivity analyses showed that our results were largely driven by the extremely low incidence of general anesthesia. If cesarean delivery rates in the United States remained at 32% of all births, the general anesthetic rate would have to be greater than 11% to achieve cost benefit. The only cost-effective strategy is to keep a 250-mg dose of dantrolene on the unit for starting therapy. Conclusions: It is not of cost benefit to maintain a fully stocked malignant hyperthermia cart with a full supply of dantrolene within 10 min of maternity units. We recommend that hospitals institute alternative strategies ( e.g ., maintain a small supply of dantrolene on the maternity unit for starting treatment). Abstract : Cost-benefit analysis showed that the costs associated with maintaining a malignant hyperthermia cart with a full dantrolene supply within 10 min of a maternity unit exceeded the benefits. Modeling suggested that a more cost-effective approach would be to keep just an initial dose of dantrolene on the maternity unit, with a central supply of dantrolene available within 30 min.